2015
DOI: 10.1093/nar/gkv787
|View full text |Cite
|
Sign up to set email alerts
|

Reassignment of a rare sense codon to a non-canonical amino acid inEscherichia coli

Abstract: The immutability of the genetic code has been challenged with the successful reassignment of the UAG stop codon to non-natural amino acids in Escherichia coli. In the present study, we demonstrated the in vivo reassignment of the AGG sense codon from arginine to l-homoarginine. As the first step, we engineered a novel variant of the archaeal pyrrolysyl-tRNA synthetase (PylRS) able to recognize l-homoarginine and l-N6-(1-iminoethyl)lysine (l-NIL). When this PylRS variant or HarRS was expressed in E. coli, toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 57 publications
3
95
0
1
Order By: Relevance
“…S7 and Dataset S5). Consistent with the findings of Mukai et al (25) and Baba et al (31), argW (tRNA Arg CCU ; decodes AGG only) was dispensable in C123a because it can be complemented by argU (tRNA Arg UCU ; decodes both AGG and AGA). However, argU is the only E. coli tRNA that can decode AGA and remains essential in C123a, probably because it is required to translate the AGR codons for the rest of the proteome (23).…”
Section: C-terminal Overlap (Mutation)supporting
confidence: 87%
See 2 more Smart Citations
“…S7 and Dataset S5). Consistent with the findings of Mukai et al (25) and Baba et al (31), argW (tRNA Arg CCU ; decodes AGG only) was dispensable in C123a because it can be complemented by argU (tRNA Arg UCU ; decodes both AGG and AGA). However, argU is the only E. coli tRNA that can decode AGA and remains essential in C123a, probably because it is required to translate the AGR codons for the rest of the proteome (23).…”
Section: C-terminal Overlap (Mutation)supporting
confidence: 87%
“…Although the translation function of the AGG codon has been shown to permit efficient suppression with nonstandard amino acids (24)(25)(26), AGG necessarily remains translated as Arg in each of these studies. No study has yet demonstrated that all instances of any sense codon can be removed from essential genes.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the rarest E. coli sense codon, AGG, was recoded from arginine (Arg) to L-homoarginine (LHR) using various tricks: all the AGG codons in essential genes were replaced with synonymous ones, the cellular levels of competing tRNAs Arg were eliminated/reduced, and a heterologous PylRS / tRNA Pyl CCU mutant specific for LHR was expressed. [21] In another example, it was possible to liberate the rare isoleucine codon AUA from its natural decoding mechanism. This was achieved by eliminating the enzyme catalyzing the tRNA modification C-to-L (2-lysyl-cytidine) at the wobble position of tRNA Ile CAU, which is important for codon recognition, and by rescuing the engineered cells with an heterologous IleRS / tRNA Ile UAU pair.…”
Section: "Rewiring" the Genetic Code: Sense Codons Reassignmentmentioning
confidence: 99%
“…Several groups have deleted RF1 in an attempt to reassign UAG to a sense codon in E. coli by subsequently introducing an orthogonal aaRS–tRNA 3338 pair to incorporate a non-canonical amino acid. Notably, when the native UAG codons are present, deleting RF1 and reassigning UAG as a sense codon causes severe growth defects 34,35 .…”
Section: Codon Reassignmentmentioning
confidence: 99%